Effects of Sitagliptin Treatment on Dysmetabolism, Inflammation, and Oxidative Stress in an Animal Model of Type 2 Diabetes (ZDF Rat) - Liliana Ferreira; Edite Teixeira-; Filipa Pinto; Belmiro Parada; Cristina Mega; Helena Vala; Rui Pinto; Patrícia Garrido; José Sereno; Rosa Fernandes; Paulo Santos; Isabel Velada; et al. (Hindawi Limited, 2010)
The purpose of this paper is to evaluate the chronic effect of sitagliptin on metabolic profile, inflammation, and redox status in the Zucker Diabetic Fatty (ZDF) rat, an animal model of obese type 2 diabetes. Diabetic and obese ZDF (fa/fa) rats and their controls (ZDF +/+) were treated during 6 weeks with vehicle (control) and sitagliptin (10 mg/kg/bw). Glucose, HbA1c, insulin, Total-c, TGs, IL-1β, TNF-α, CRPhs, and adiponectin were assessed in serum and MDA and TAS in serum, pancreas, and heart. Pancreatic histology was also evaluated. Sitagliptin in diabetic rats promoted a decrease in glucose, HbA1c, Total-c, and TGs accompanied by a partial prevention of insulinopenia, together, with a decrease in CRPhs and IL-1β. Sitagliptin also showed a positive impact on lipid peroxidation and hypertension prevention. In conclusion, chronic sitagliptin treatment corrected the glycaemic dysmetabolism, hypertriglyceridaemia, inflammation, and hypertension, reduced the severity of the histopathological lesions of pancreatic endocrine and exocrine tissues, together with a favourable redox status, which might be a further advantage in the management of diabetes and its proatherogenic comorbidities.